1999
DOI: 10.1046/j.1365-2672.1999.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

A highly thermostable amylase from a newly isolated thermophilicBacillussp. WN11

Abstract: A thermostable amylase-producing Bacillus sp. WN11 was isolated from Wondo Genet hot spring in Ethiopia. The enzyme had a temperature optimum of 75-80°C. Over 80% of its peak activity was in the pH range of 5-8, with an optimum at 5·5. Thermal stability of the enzyme at 105°C was higher with the addition of starch. The stabilizing effect of starch was concentrationdependent, showing better stability with increasing concentration of starch. At liquefying temperature (105°C), addition of Ca 2+ did not result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The addition of 2 − 5% soluble starch delayed the decrease in the activity of Thermomonospora fusca α-amylase incubated at 70℃ (Busch and Stutzenberger, 1997) and delayed the decrease in the activity of thermophilic Bacillus sp. WN11 incubated at 105℃ (Mamo et al, 1999). These studies concluded that starch had a stabilizing effect on amylase, although they did not measure k 0 and E a values.…”
Section: Results and Discussion α-Amylase Activity At High Temperaturesmentioning
confidence: 97%
“…The addition of 2 − 5% soluble starch delayed the decrease in the activity of Thermomonospora fusca α-amylase incubated at 70℃ (Busch and Stutzenberger, 1997) and delayed the decrease in the activity of thermophilic Bacillus sp. WN11 incubated at 105℃ (Mamo et al, 1999). These studies concluded that starch had a stabilizing effect on amylase, although they did not measure k 0 and E a values.…”
Section: Results and Discussion α-Amylase Activity At High Temperaturesmentioning
confidence: 97%
“…There are several studies demonstrating the effects of metal ions on bacterial and fungal α-amylases. Although, any specific ion is not required for the catalytic activity of amylase but there are several reports on the Ca 2+ dependent α-amylase from Bacillus spp [25,[40][41][42][43]. It has been reported that α-amylase is a metalloenzyme containing at least one activating Ca 2+ ion.…”
Section: Effect Of Metal Ions On α-Amylase Activitymentioning
confidence: 99%
“…WN11, a thermophile earlier isolated in our laboratory (Mamo et al 1999). The basal medium used was composed of (g/l): NaCl, 1; KH2PO4, 2; CaCl2, 0·1; MgSO4, 0·1; and trace mineral solution, 20 ml.…”
Section: The Organism and Cultivation Conditionsmentioning
confidence: 99%
“…Amylase activity was assayed based on the amount of reducing sugar released following the dinitrosalicylic acid (DNS) method as described previously (Mamo and Gessesse 1997). One unit of amylase activity was defined as the amount of enzyme that released 1 mmol of reducing sugar equivalent to glucose per min under the assay condition.…”
Section: Enzyme Assaymentioning
confidence: 99%
See 1 more Smart Citation